Synthesis of N-methyl-4-piperidone Curcumin Analogues and Their Cytotoxicity Activity against T47D Cell Lines - Yum Eryanti; Rudi Hendra; Tati Herlina; Adel Zamri; Unang Supratman (Universitas Gadjah Mada, 2018)
Three piperidone curcumin analogues (N-methyl-(3E,5E)-3,5-bis-(2-chlorobenzylidene)-4-piperidone (1), N-methyl-(3E,5E)-3,5-bis-(3-bromobenzylidene)-4-piperidone (2) and N-methyl-(3E,5E)-3,5-bis-(4-chlorobenzylidene)-4-piperidone (3)) were synthesized from N-methyl-4-piperidone with halogenbenzaldehyde, 2-chlorobenzaldehyde, 3-bromobenzaldehyde and 4-chlorobenzaldehyde. The Claisen-Schmidt condensation reaction was used in alkali condition with combinatorial. All the compounds showed light yellow needle, light yellow powder, and yellow crystal form with percentage of yield 39, 66, and 40%, respectively. All the structure compounds were confirmed by using UV, IR, 13C-NMR, 1H-NMR and MS. Apart from that, the cytotoxicity results against breast cancer cell (T47D) showed strong to moderate activity with the IC50 value 8, 4, and 45 µg/mL, respectively.